Advances in the Synthesis of Morpholin-3-ones and Morpholin-2-ones - Trstenjak, Uroš; Ilaš, Janez; Kikelj, Danijel (Synthesis, 2012)
This review covers advances in the synthesis of morpholin-3-ones and morpholin-2-ones. Besides the classical approaches for the preparation of both heterocycles that utilize intermolecular cyclizations of reactants or oxidation of morpholine and its derivatives, strategies employing various ring-expansion reactions using smaller heterocyclic substrates or multicomponent reactions are described.1 Introduction2 Synthesis of Morpholin-3-ones2.1 By Formation of Two Bonds2.2 By Formation of One Bond2.3 By Introduction of Substituents3 Synthesis of Morpholin-2-ones3.1 By Formation of Two Bonds3.2 By Formation of One Bond3.3 By Introduction of Substituents4 Conclusion
Keywords: morpholin-3-one; morpholin-2-one; one-bond cyclization; two-bond cyclization; heterocycle oxidation